2016
DOI: 10.14710/reaktor.16.2.81-86
|View full text |Cite
|
Sign up to set email alerts
|

Peranan Pengadukan Terhadap Karakteristik Kompleksasi Urea Sebagai Sarana Pemisahan Asam Lemak Omega Dari Minyak Nabati

Abstract: MIXING-TIME EFFECTS OF THE UREA COMPLEXATION CHARACTERISTICS FOR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…The difference in viscosity/viscosity can also be caused by the type of vegetable oil used, with the characteristics of each vegetable oil being different. This theory is in line with the opinion of Setyawardhani et al that each type of vegetable oil has different characteristics depending on the fatty acid content contained in it besides vegetable oil which acts as an internal phase that greatly affects the viscosity of mayonnaise so that at different concentrations it will make a difference to the viscosity of mayonnaise [21]. The viscosity (cP) value of mayonnaise is shown in Table 4.…”
Section: Viscosity Analysis Of Mayonnaisesupporting
confidence: 81%
“…The difference in viscosity/viscosity can also be caused by the type of vegetable oil used, with the characteristics of each vegetable oil being different. This theory is in line with the opinion of Setyawardhani et al that each type of vegetable oil has different characteristics depending on the fatty acid content contained in it besides vegetable oil which acts as an internal phase that greatly affects the viscosity of mayonnaise so that at different concentrations it will make a difference to the viscosity of mayonnaise [21]. The viscosity (cP) value of mayonnaise is shown in Table 4.…”
Section: Viscosity Analysis Of Mayonnaisesupporting
confidence: 81%
“…Number of double bonds provide the greater diameter of the molecule. Thus, it gives some difficulties for the unsaturated molecules to form an inclusion with urea [8].…”
Section: Table 2 the Process Variables In The Urea Complexationmentioning
confidence: 99%
“…The effect of the ratio of urea/FFA and urea/ethanol to the fatty acids in concentrate has been studied. The results showed that the ratio of urea/FFA was linear with fatty acid content [14]. Optimization of urea crystallization of lemuru fish oil for omega-3 concentrate production had been studied by using one-step urea complexation; the results showed that the ratio of the urea-fatty acid was optimum at 2:1 at 24 hours [15].…”
Section: Introductionmentioning
confidence: 99%